Longitudinal Analysis of Anti-cardiolipin and Anti-β2-glycoprotein-I Antibodies in Recent-Onset Systemic Lupus Erythematosus: A Prospective Study in Swedish Patients - Frodlund, Martina; Walhelm, Tomas; Dahle, Charlotte; Sjöwall, Christopher (Frontiers in Medicine, 2021)
Abstract Background: Anti-phospholipid syndrome (APS) and systemic lupus erythematous (SLE) are autoimmune disorders that often co-occur. Anti-phospholipid antibodies (aPL) are typical of both conditions and may be associated with vascular events and pregnancy-related morbidities. Whereas aPL-screening is mandatory for individuals with suspected SLE, the clinical value of longitudinal aPL analyses in established SLE is unclear. Methods: We investigated the occurrence and variation of IgG/IgA/IgM anti-cardiolipin (aCL) and anti-β2-glycoprotein-I (anti-β2GPI) antibodies, using both the manufacturer’s cut-off and a cut-off based on the 99th percentile of 400 apparently healthy donors, in recent-onset SLE. Furthermore, we evaluated the relationships between aPL levels and SLE/APS manifestations, as well as the pharmacotherapy. Patients with SLE who met validated classification criteria were included in this prospective study (N=54). Samples were obtained at 0, 6, 12, 24, 36, 48, 60, 72, 84 and 96 months after SLE diagnosis. Results: Depending on the cut-off applied, 61.1% or 44.4% showed a positive result for at least one aPL isotype or the lupus anticoagulant test over time. Median values for all six aPL isotypes numerically decreased from inclusion to last follow-up, but none of the isotypes met statistical significance. Seroconversion (from positive to negative, or the opposite direction) was occasionally seen for both aCL and anti-β2GPI. IgA and IgM anti-β2GPI were the most common isotypes, followed by IgM aCL. Presence of IgG aCL associated significantly with myocardial infarction and miscarriage, and IgG/IgA anti-β2GPI with miscarriage. Conclusion: aPL were common during the first years of SLE. Even though the levels fluctuated over time, the patients tended to remain aPL positive or negative. Repeated aPL testing in the absence of new symptoms seems to be of uncertain value in patients with recent-onset SLE.